Assessing the accuracy of projected entangled-pair states on infinite lattices - Bauer, Bela; Vidal, Guifre; Troyer, Matthias (Journal of Statistical Mechanics: Theory and Experiment, 2009)
Generalizations of the density-matrix renormalization group method have long been sought after. In this paper, we assess the accuracy of projected entangled-pair states on infinite lattices by comparing with Quantum Monte Carlo results for several non-frustrated spin-1/2 systems. Furthermore, we apply the method to a frustrated quantum system.